The Effects of Frugal Innovation, Strength-Based Approach, and Social Media on The Longevity of Small Businesses in Jakarta in 2021 - Meisya Claudia; Andi Wijaya (Graduate Program of Universitas Tarumanagara, 2023)
Small businesses are one of the largest supporting countries for the country's gross domestic product in Indonesia with a percentage of more than sixty percent. However, the ratio of entrepreneurship in Indonesia is still very small compared to neighboring countries with a value of three point forty-seven percent. The purpose of this study was to empirically examine the effect of frugal innovation on the longevity of small businesses in Jakarta in 2021, the effect of a strength-based approach on the longevity of small businesses in Jakarta in 2021, and the effect of social media on the longevity of small businesses. Small businesses in Jakarta in 2021. The sampling in this study used the non-probability sampling method and convenience sampling technique. The number of samples in this study were 200 respondents and the data was processed using the SmartPLS application, where the results showed a positive influence from frugal innovation on the longevity of small businesses in Jakarta in 2021, a positive influence from the strength-based approach on the longevity of small businesses. Small business in Jakarta in 2021, and a positive influence of social media on the longevity of small businesses in Jakarta in 2021.